The myth of the benevolent autocrat? Internal constraints, external constraints, and economic development in autocracies - Nyrup, J (2020)
Why do some autocracies produce high economic development while others falter? Despite the large literature comparing democracies and autocracies we know little about differences amongst autocratic regimes. I focus on the rule of one autocrat over time instead of comparing across regimes, and argue that an autocrat can be constrained by both a strong ruling elite (internal constraints) and an organized civil society (external constraints). I depart from the literature focusing on institutional constraints and use Arendt’s concept of isolation to conceptualize constraints. The two types of constraints generate political accountability. This will result in a pluralistic and thoughtful decision-making process and a better environment for investment. I theorize that both types of constraints are associated with better economic outcomes, but that only external constraints promote better human development. To test this, I rely on three analyses. First, I conduct a cross-national analysis using a novel dataset, WhoGov, which provides information on the ruling elites. I show that only constrained autocrats are punished for governing over a severe recession. Furthermore, the same dictator governs over better economic outcomes when his rule is constrained. That said, only external constraints are related to improvements in human development. Second, I use a synthetic control design to investigate the effect of the Tulip Revolution in Kyrgyzstan, and show that the regime, despite not democratizing, increased public spending on health care and education. Third, I show that there is a cost to the ruling elite if they unsuccessfully try to coup the autocrat. In addition, I find that a successful coup is associated with better growth when there is an orderly transfer of power to a new, constrained autocrat, but not if the coup causes political instability. Overall, I show that the belief in the developmental benefits of having a strong autocrat is not supported empirically. Instead, autocrats govern over worse economic development when they become more powerful.